Dampak Industri Halal pada Perekonomian di Indonesia: Pengaruh Pendapatan, Ekspor, dan FDI terhadap PDB Melalui Pendekatan GMM - Zul Ihsan Mu'arrif (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research explores the influence of income, exports and foreign direct investment (FDI) on Gross Domestic Product (GDP) in the halal industry in Indonesia, using the Generalized Method of Moments (GMM) approach. This study is based on panel data from companies operating in the halal sector between 2010 and 2022. The results show that income and exports positively and significantly influence GDP growth, confirming the importance of company activities and export performance in driving national economic growth. In contrast, FDI was found to have no significant effect on GDP, indicating that foreign investment's contribution in this sector is not yet optimal or is influenced by other factors such as the quality of institutions and infrastructure. This research provides important implications for policymakers and stakeholders, considering the urgency of improving export strategies, diversifying markets, and improving the quality of institutions and infrastructure to maximize the economic benefits of FDI. In addition, the results of this research also emphasize the important role of the halal industry as a major contributor to Indonesia's economic growth, as well as the need for policies that support further development and diversification of the halal industrial sector.